2009
DOI: 10.1111/j.1600-0633.2009.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural transition during the estuarine migration of wild Atlantic salmon (Salmo salar L.) smolt

Abstract: –  Ultrasonic telemetry and hydrodynamic modelling were used to study the migratory behaviour of 54 wild Atlantic salmon (Salmo salar) smolt captured in freshwater during their downstream migration and tracked in 2 years through a shallow estuary system. A high‐density, fixed array of receivers provided detailed spatial and temporal resolution of behaviour in the second year of study. Smolt migration in the river occurred mostly at night and downstream migration was slower during the day. In the estuary, smolt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 36 publications
(89 reference statements)
7
53
0
1
Order By: Relevance
“…However, other studies have demonstrated that water currents are not systematically used as an orientation cue, because smolts often show random movements compared to the water current direction [27,31]. It has also been suggested that positive salinity gradients may be one of the key factors for seaward movements [6,26]. Our results support that post-smolts may exploit variation in salinity cues for navigation purposes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, other studies have demonstrated that water currents are not systematically used as an orientation cue, because smolts often show random movements compared to the water current direction [27,31]. It has also been suggested that positive salinity gradients may be one of the key factors for seaward movements [6,26]. Our results support that post-smolts may exploit variation in salinity cues for navigation purposes.…”
Section: Discussionsupporting
confidence: 78%
“…A preference for low salinities in the first phase of the marine migration may furthermore be related to acclimatization to sea water, because the transfer from freshwater to sea water involves considerable osmoregulatory stress [24]. Although several studies have shown that post-smolts migrate in the upper few metres of the water column [6,25,26], little is known about the salinity they actually experience in situ, and how they respond to variation in salinity.…”
Section: Open Accessmentioning
confidence: 99%
“…Other laboratory experiments have found no period of acclimation occurred for smolts upon reaching salt water (Moore et al 1995). It is, however, possible that fish use tidal movements to minimize energetic costs, especially because this is the period of migration during which smolts are thought to transition from passive to active migration (Hedger et al 2008;Martin et al 2009). Further investigation of diurnal and tidal factors that influence behavior and survival on localized spatial and temporal scales could provide an improved understanding of those mechanisms and might have implications for strategic stocking of hatchery-reared smolts.…”
Section: Atlantic Salmon Smolts During Estuary Migrationmentioning
confidence: 99%
“…The reduction in movement rates through estuaries might also result from the reversal of migratory direction during the passage of tidal estuaries and bays (Kocik et al 2009;Dempson et al 2011;Halfyard et al 2013). These behaviors appear to be related to tidal cycles in both estuarine (McCleave 1978;Martin et al 2009) and coastal systems (Lacroix et al 2005). This behavior previously has been hypothesized to relate to saltwater acclimation (Gudjonsson et al 2005;Dempson et al 2011;Halfyard et al 2013).…”
Section: Atlantic Salmon Smolts During Estuary Migrationmentioning
confidence: 99%
“…The smoltification process is the physiological and morphological transition that enables these fish to switch from a freshwater-adapted metabolism to a marine pelagic lifestyle, and that also marks a behavioural shift from resident to migratory behaviour (Hoar 1976, Gribson 1983, Martin et al 2009). Cultured salmon are transferred from the hatchery to cages in the sea at the smolt stage.…”
Section: Introductionmentioning
confidence: 99%